Nonequilibrium transport properties of a double quantum dot in the Kondo regime - Breyel, David; Komnik, Andreas (Physical review. B, Condensed matter and materials physics, 2011)
We analyze the nonequilibrium transport properties of a parallel double quantum dot in terms of its full counting statistics (FCS). The parameters of the setup are assumed to be such that both subsystems are driven into the Kondo regime. After a series of transformations, the Hamiltonian is then mapped onto a Majorana resonant level model, which effectively describes the Toulouse point of the respective double-impurity two-terminal Kondo model. Its FCS is then obtained at arbitrary constellation of voltage, temperature, and local magnetic fields. We identify two different transport processes corresponding to single-electron tunneling as well as an electron pair process, and we give the respective effective transport coefficients. In the most universal linear-response regime, the FCS turns out to be of a binomial shape with an effective transmission coefficient. Furthermore, we find a complete transport suppression (antiresonance) at a certain parameter constellation, which is similar to the one found in the noninteracting quantum dots. By an explicit expansion around the Toulouse point, we show that the antiresonance is universal and should be observable in the generic Kondo dot setup. We discuss experimental implications of our predictions as well as possible routes for generalizations of our approach.